Agricultural Productivity and Forest Conservation: Evidence from the Brazilian Amazon. (12th March 2019) - Koch, Nicolas; zu Ermgassen, Erasmus K H J; Wehkamp, Johanna; Oliveira Filho, Francisco J B; Schwerhoff, Gregor
Abstract: A mix of public policy and market interventions in the mid-2000s led to historic reductions in deforestation in the Brazilian Amazon. The collateral impact of these forest conservation policies on agricultural production is still poorly understood, though evidence is sorely needed given the economic importance of agriculture in Brazil and many other forest-rich countries. We construct a ten-year panel dataset for agriculture and deforestation in the Brazilian Amazon (2004–2014), and use two complementary difference-in-difference strategies to estimate the causal effect of one of Brazil's flagship anti-deforestation strategies, the Priority List (Municípios Prioritários), on agricultural production and productivity in three sectors: beef, dairy, and crop production. We find no evidence for trade-offs between agriculture and forest conservation. Rather, reductions in deforestation in priority municipalities were paired with increases in cattle production and productivity (cattle/hectare), consistent with a model where policy-induced decreases in the value of clearing new land cause credit-constrained farmers to shift investments from deforestation to capital investments in farming. The policy had no consistent effect on dairy or crop production. Our results suggest that in regions with large yield gaps and where technologies for increasing yields are readily available, efforts to constrain agricultural expansion through improved forest conservation policies may induce intensification.